Fuel-efficient exhaust thermal management using cylinder throttling via intake valve closing timing modulation. (March 2016) - Garg, Akash; Magee, Mark; Ding, Chuan; Roberts, Leighton; Shaver, Greg; Koeberlein, Edward; Shute, Ray; Koeberlein, David; McCarthy, James; Nielsen, Douglas
Most diesel engines meet today's strict NOx and particulate matter emission regulations using after-treatment systems. A major drawback of these after-treatment systems is that they are efficient in reducing emissions only when their catalyst temperature is within a certain range (typically between 250  °C and 450 °C). At lower engine loads this is a major problem as the exhaust temperatures are usually below 250 °C. The primary objective of this study was to analyze "cylinder throttling" via both delayed and advanced intake valve closure timing. The effect of cylinder throttling on exhaust gas temperatures, fuel consumption, in-cylinder combustion and emissions is outlined. A significant increase in turbine outlet temperature accompanied by a decrease in fuel consumption, NOx, and particulate matter emissions was observed. Both delayed and advanced intake valve closure timings were equally effective. The increase in exhaust gas temperatures was attributed to a drop in air flow through the engine, which resulted from a reduction in the volumetric efficiency via cylinder throttling. The increase in fuel efficiency resulted from a decrease in the pumping work through a reduction in air flow through the engine. Reductions in NOx are attributed to the combined effect of a lower in-cylinder temperature due to a reduction in piston-motion-induced compression and a shift to a more premixed combustion mode. Particulate matter emissions were also reduced as a result of additional premixing. At the 1200 RPM and 2.5 bar brake mean effective pressure (BMEP) operating point, both delayed and advanced intake valve closure timings resulted in a turbine outlet temperature increase from 195 °C to 255 °C accompanied by an increase in brake thermal efficiency of 1.5% (absolute) and a reduction in brake-specific NOx and particulate matter emissions by 40% and 30%, respectively.